Basics of polymers : fabrication and processing technology. - Muralisrinivasan Subramanian (Plastics and Polymers Collection)
Basics of Polymers: Fabrication and Processing Technology constitutes one of the most important aspects of polymer science and technology. The performance of polymers is evolving into the most rapidly increasing volume of production. Polymers are an important commodity in the modern lifestyle. They are undoubtedly superior materials in terms of their costs, processability, and functional properties. The fabrication and processing technology are showing higher growth than that of the number of polymer grades in the market. This book is a noteworthy text in the increasingly important field of p.